The Priesthood of All Sentients? The Eclipse of Transcendence in an Age of Artificial Intelligence - Saragih, Denni Boy (Veritas : Jurnal Teologi dan Pelayanan, 2023)
BlessU-2 is a robot and a specifically designed anthropomorphic machine that performed a blessing service during 2017’s exhibition in Wittenberg, Germany, commemorating 500 years of the reformation. The exhibition was intended to open a conversation about the future of the church’s service and AI’s role in it. This research explores and introduces today’s AI research development and theological challenges for ecclesiology and Christian worship. The research explores the theological themes that can be employed by Christian theology in general and ecclesiology in particular. It proposes that the main challenge of AI developments is the reinterpretation of the transcendent in the form of AI in which technology is perceived as godlike. On the other hand, AI fills a void in the religious lacuna that reaffirms the yearning for meaning and connection. Finally, the paper proposes the importance of the basic human nature of relationality in an age of simulated artificial reality.